Tutankhamon em Portugal (1923-1926): Da superstição ao ensaio académico ou os percursos que vão da «maldição da múmia» ao Hino a Aton - José das Candeias Sales; Susana Mota (História - Revista da Faculdade de Letras da Universidade do Porto, 2018)
The discovery of the tomb of Tutankhamon, in 1922, was reported by the international press all round the world, including Portugal. Between us, from 1923 to 1926, the fabulous archaeological find was reported by the press (valuing the superstitious thesis of the "mummy's curse"), by the publication of Fernando de Carvalho Henriques’s Tut-Ankh-Amon's crime novel A Profecia ou O Mistério da Morte de TutAnk-Amon by (which is the first novel ever published at an international level inspired by the great Egyptian archaeological discovery), and by the academic essays of Humberto Pinto de Lima in the journal Dionysos (that includes the first translation to Portuguese of the Hymn to Aton)